PENGENDALIAN KUALITAS PEMOTONGAN KAIN SATEN PADA PROSES PEMBUATAN TAS DI HOME INDUSTRI X DI KABUPATEN SIDOARJO - Putri, Erni Puspanantasari (Heuristic, 2016)
purchasing power, making a number of craftsmen home industry in Sidoarjo either small, medium or produced in homes facing bankruptcy. Their products are not only competing with a medium or large industrial products that use semi-modern machinery, but also imported products, especially from China and Vietnam which relying on cheaper product prices. Ironically, consumers now also its orientation, to model and quality. It which not owned by the craftsman home industry, because their manual production. With this condition, resulted in the emergence difficulties for home craftsmen in the industry to improve and expand its business. With the variety of backgrounds, as described above, the purpose of this research are to provide recommendations about the quality control, cutting sateen in the process of making bags in the Home Industries X. Solving problems in this research using the method to determine the source of variation of the process, that is using the Control Chart of X-bar (average) and R (Range). The results showed that the value of Process Capability Index (Cp) in the Home Industry X has a value of Cp = 0.525 <1.00. This means that the process has a low capability to meet the specifications of the expected measurement. As well as with size of Kane Performance Index (Cpk = 0.367) were the criteria CPL = 0.367, or CPU = 0.682 <1.00, which means that the process is not able to meet the lower specification limit (LSL) and upper (USL). With this condition, it is necessary to control the use of control chart from the X-bar and R to monitor the ongoing process from time to time, to so quickly take corrective action, if any changes which not desirable in the process of making bags at Home industrial X. Kata Kunci : Pengendalian Kualitas, Indek Kapabilitas Proses (Cp), Indeks Kinerja Kane (Cpk)